Characterization of Ustilago segetum causing loose smut of wheat - Kaur, G; Sharma, I; Sharma, R C (Journal of Cereal Research, 2011)
Isolates of loose smut of wheat caused by Ustilago segetum (Pers.) Roussel tritici Jensen were collected from different cultivars of wheat grown at various locations of North-Western Indi (Punjab, Haryana, U.P. and Rajasthan). The genetic relationships of molecular variability and and virulence pattern among these races is unknown. In this study, a total of 24 isolates of representing six groups of U. segetum tritici were studied using molecular and virulence data. In total, eighteen random decamer primers and ISSR primers were used to characterize twenty four isolates of the pathogen. The RAPD and ISSR primers were used for polymorphism analysis and generated a total of 206 scorable bands collectively. All the isolates could be precisely differentiated from each other employing these primers and grouped into two distinct clusters. The classification at molecular level did not exactly collate with the geographical distribution of the isolates and virulence / pathogenicity.